Anti‐inflammatory phenylpropanoid glycosides from the roots of Polygala aureocauda Dunn. Issue 5 (25th October 2019) - Quang, Tran Hong; Yen, Duong Thi Hai; Dung, Duong Thi; Trang, Do Thi; Ngan, Nguyen Thi Thanh; Van Kiem, Phan; Van Minh, Chau
Abstract: Chemical study on a methanol extract of the roots of Polygala aureocauda Dunn. resulted in the isolation of three phenylpropanoid glycosides, including β‐D‐[3‐ O ‐(3, 4, 5‐trimethoxycinnamoyl)]‐fructofuranosyl‐α‐D‐[6‐ O ‐(4‐methoxybenzoyl)]‐glucopyranoside (1 ), β‐D‐(3‐ O ‐sinapoyl)‐fructofuranosyl‐α‐D‐(6‐ O ‐sinapoyl)‐glucopyranoside (2 ), and tenuifoliside C (3 ). Their chemical structures were elucidated by NMR and MS spectroscopic analysis in comparison with the data reported in the literature. Of the isolates, compound 1 inhibited NO and PGE2 overproduction in LPS‐stimulated RAW264.7 macrophages, with IC50 value of 29.7 and 28.7 μM. These effects of 1 were shown to be related to its suppressive effects on iNOS and COX‐2 protein expression.